Analysis of Perception and Compliance of Sibolga Purse Seine Fishermen Based on Licensed Fishing Ground - Rahayu, Rosi; Fuah, Ricky Winrison (Journal of Fish Health, 2025)
The purse seine fishery in Sibolga plays a vital role in fish production but faces challenges regarding compliance with licensed fishing ground regulations. Non-compliance, driven by economic pressure and declining fish stocks, threatens resource sustainability and fishermen’s welfare. This study aimed to analyze fishermen’s perceptions and compliance levels regarding the use of licensed fishing areas and their relationship to regulatory enforcement. The research was conducted from January-March 2024 at Sibolga Archipelago Fishing Port, North Sumatra, one of the main landing bases for purse seine vessels. Data were collected from 115 respondents, consisting of vessel captains and mates, using structured questionnaires and direct interviews. Observations and secondary data from fisheries institutions supported the primary data. Data were analyzed using descriptive statistics and the non-parametric Kruskal–Wallis test to determine differences in perceptions and compliance among fishing groups categorized by vessel tonnage and fishing zones. The results showed that fishermen’s perceptions of potential fishing grounds and fish resource availability were relatively uniform across groups, indicating a shared view that fishing effort continues to expand to secure catches. In contrast, perceptions of VMS usage differed significantly, with the 30–100 GT small pelagic purse seine group acknowledging its role in detecting violations. Compliance levels also varied, with the 30–100 GT small pelagic purse seine operating in <12-mile zones showing the lowest compliance. It is concluded that stricter enforcement, effective monitoring, and targeted empowerment programs are necessary to enhance compliance and ensure sustainable fisheries management in Sibolga.